Associations between javelin throwing technique and aerodynamic distance - Leigh, S.; Liu, H.; Yu, B. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The javelin is the most aerodynamic of the four track and field throwing implements. It is twenty times more aerodynamic than the discus (Hubbard, 1984). The official distance of a throw is measured by the meet officials. The vacuum flight distance is determined by the release parameters and the range equation. The aerodynamic distance is the distance gained (where official distance is greater than vacuum flight distance) or lost (where official distance is smaller than vacuum flight distance) due to aerodynamic factors that affect the flight (Hay & Yu, 1995). The ability to gain aerodynamic distance may be the differentiating factor between athletes with near-maximal release speeds and vacuum flight distances. It may be possible for a javelin thrower to increase their aerodynamic distance independently of other performance variables, such as release speed. A javelin throwers technique determines the release parameters of the javelin, which determines the aerodynamic distance. The purpose of this study was to determine which technique variables are associated with greater aerodynamic distances.